KONSEP TOLERANSI DAN KEADILAN SOSIAL NABI MUHAMMAD SAW DALAM KITAB AL-RAḤĪQ AL-MAKHTŪM SEBAGAI BASIS PENDIDIKAN MULTIKULTURAL - Muhammad Jallaluddin; Nashrullah; Muhammad Indra Wahyu Kurnia; Ibnii Irsadul Abidin; Muhammad Zulfa Muzayin (Journal Multicultural of Islamic Education, 2024)
This study examines the concepts of tolerance and social justice of Prophet Muhammad SAW in the book Al-Raḥīq al-Makhtūm by Shafiyyurrahman Al-Mubarakfuri and their relevance as the basis of multicultural education in the modern era. This research uses a qualitative approach with the type of library research. The primary data source is the book Al-Raḥīq al-Makhtūm, while secondary sources are obtained from books, journals, and relevant scientific articles discussing multicultural education, tolerance, and social justice. Data collection was conducted through documentation techniques, while data analysis used content analysis with a descriptive-analytical approach. The results show that the Prophet Muhammad SAW practiced tolerance through recognition of social diversity, protection of minority rights, freedom of religion through the Medina Charter, and inclusive social interaction. The concept of social justice is reflected in equality before the law, protection of human rights, rejection of discrimination, and fair distribution of social rights. These values are highly relevant to multicultural education in the modern era, especially in building inclusive, democratic, and humane educational systems. This study contributes to strengthening Islamic-based multicultural education by positioning the prophetic values contained in Al-Raḥīq al-Makhtūm as conceptual and practical foundations in responding to intolerance and social discrimination in contemporary society.